PERHITUNGAN KEBUTUHAN JUMLAH INDUK SAPI UNTUK MENDAPATKAN KEUNTUNGAN USAHA YANG MAKSIMAL MENGGUNAKAN METODE LAGRANGIAN DI KABUPATEN MANOKWARI: THE NEED NUMBER OF COWS CALCULATION TO ACHIEVE MAXIMUM BUSINESS PROFIT USING LAGRANGIAN METHOD IN THE DISTRICT OF MANOKWARI - Trisiwi Wahyu Widayati (Fakultas Peternakan Universitas Papua, 2012)
This study was carried out in Manokwari District to the determinants of the amount of beef which is needed by beef farmer household in order to get maximum profit. Data was collected from 89 farmer household. Ordinary Least Square regression model and lagrangian optimalization method were used to analyze the primary data obtained from the survey conducted. The findings of the study showed that the number of cows which was needed to produce maximum profit are 2 (two) unit on average 0, 22 acres of land and and 8 unit on 2 acres of land tenure.